Incidence and risk factors for acute kidney injury in children with nephrotic syndrome: a meta-analysis - Chen, Changdi; Qiu, Bingbing; Wang, Jianxin; Yang, Liuqing; Huang, Yanru (Frontiers in Pediatrics, 2024)
Nephrotic syndrome (NS) is a prevalent kidney disease in children. Acute kidney injury (AKI) is a severe complication of NS and has the potential to be life-threatening.The aim of this study was to analyze the prevalence and risk factors of AKI in children with NS, and to provide an evidence-based medical basis for the early identification of high-risk children in the clinic.A comprehensive search was conducted in publicly available databases, namely PubMed, Embase, Web of Science, Scopus, and the Cochrane Library, covering the period from the inception of each database until May 2024. The analysis involved examining basic characteristics (age, sex), the concomitant diseases (hypertension, infections), NS disease characteristics (steroid susceptibility classification, pathologic classification), laboratory test (e.g., serum albumin), and the use of nephrotoxic drugs. Traditional and network meta-analyses were performed for analysis.A total of 11 studies were included in the analysis, revealing an incidence of AKI of 29% (95% CI: 23%-37%). The analysis of factors indicated that the age of NS onset (standardized mean difference [SMD]: 0.31; 95% confidence interval [CI]: 0.08, 0.54; p = 0.009), sex (odds ratio [OR]: 1.49; 95%